2017
DOI: 10.3390/f8090294
|View full text |Cite
|
Sign up to set email alerts
|

Age-Effect Radial Growth Responses of Picea schrenkiana to Climate Change in the Eastern Tianshan Mountains, Northwest China

Abstract: Abstract:The climate changed from warm-dry to warm-wet during the 1960s in northwest China. However, the effects of climate change on the response of radial growth from different age-class trees have been unclear. We assessed the age-effect radial growth responses in three age-classes (ml-old: ≥200 years, ml-middle: 100-200 years and ml-young: <100 years) of Schrenk spruce (Picea schrenkiana Fisch. et Mey.) in the eastern Tianshan Mountains. The primary conclusions were as follows: the developed chronologies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…This finding is consistent with the results of other studies indicating that age indirectly affects the trees' response to environmental factors due to photosynthesis efficiency, hydraulic conductance and nutrient transport (Vieira et al 2009). Jiao et al (2017) reported that tree age could interfere with the expression of environmental signals related to radial growth and that the age effect is not completely eliminated from the developed chronologies. The KO site was the only one where1-month timescale SPEI (current April) was negatively correlated with BP growth, implying that the low amount of rainfall during this month may delay the initiation of BP radial growth.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with the results of other studies indicating that age indirectly affects the trees' response to environmental factors due to photosynthesis efficiency, hydraulic conductance and nutrient transport (Vieira et al 2009). Jiao et al (2017) reported that tree age could interfere with the expression of environmental signals related to radial growth and that the age effect is not completely eliminated from the developed chronologies. The KO site was the only one where1-month timescale SPEI (current April) was negatively correlated with BP growth, implying that the low amount of rainfall during this month may delay the initiation of BP radial growth.…”
Section: Discussionsupporting
confidence: 93%
“…Heat stress and moisture stress are the main climatic stresses in the process of tree-ring formation. These stresses have been confirmed in dendroclimatological studies using tree-ring samples of both Schrenk spruce growing in different parts of the Tianshan Mountains [47,[52][53][54] and northern spruce, pine, and juniper [19,[55][56][57]. The tree-ring chronologies of specimens at both the high and low elevation sites revealed similar climatic responses ( Figure 5).…”
Section: Discussionsupporting
confidence: 59%
“…In addition, high solar radiation in this arid area, coupled with a thin soil thickness and an open canopy, may result in high evaporative water loss (Yu et al ., ). Similar tree growth responses to climate have been frequently verified for Schrenk spruce and other species in previous studies, including P. schrenkiana in the Tianshan Mountains (Li et al ., ; Jiao et al ., ; Zhang et al ., ), Picea obovata in the Altay Mountains (Chen et al ., ), L. sibirica in Mongolia (Davi et al ., ), Picea crassifolia Kom. in the Xinglong Mountains (Liu et al ., ), and P. crassifolia and Sabina przewalskii in the northern Tibetan Plateau (Liang et al ., ).…”
Section: Discussionmentioning
confidence: 99%